Conspiracy Theories of Flight Ticket Prices Post Covid-19. - Watanapalachaikul, Sethapong (Journal of Humanities and Social Sciences, Rajapruk University, 2025)
This research aims to 1) study the conspiracy theory by analyzing economic factors and airline operating costs on airfare after COVID-19 and 2) study the opinions of travelers and experts on airfare after COVID-19. The sample groups are economic factors and airline operating costs on airfare and travelers and airline business experts. This research uses a mixed-method research method with econometric model analysis and focus group discussions. The quantitative research uses ARIMA model and Structural Break Analysis to analyze historical airfare data between Australia and Thailand during 2020–2023. The data is collected from public sources such as airline websites and industry databases, and GRETL program is used for analysis. The model quality is checked with Chow Test and CUSUM Test. The qualitative research uses focus group discussions (FGDs) with experts from various fields in the aviation industry and passengers to analyze the content from the main themes of price changes after COVID-19. The quantitative research results show that airfare prices have increased due to inflation, fuel costs, economic recovery, border openings, and increased operating costs. Economic factors significantly impacted price changes across all airlines studied in the post-COVID period, consistent with significant conspiracy theories. Qualitative findings suggest that rising airfares after COVID-19 have dissatisfied travelers, with experts pointing to fuel and labor costs as key factors. Some travelers believe that airlines are raising prices unnecessarily and lacking transparency, which has changed travel behavior, with general travelers reducing their trips and business travelers being less affected. Conspiracy theories suggest that airlines are taking advantage of the fallout from the pandemic to artificially adjust prices based on economic and cost factors and raise prices collusively. Airlines should therefore increase transparency in their pricing strategies and improve their communication with consumers to build trust in airfares.